IMPLEMENTASI PROGRAM KARTU TANDA PENDUDUK ELEKTRONIK (E-KTP) DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN MELAWI - Via Octiwi E42009058 (FISIP Universitas Tanjungpura Pontianak, 2021)
Essay writing on the implementation of the electronic population sign card program is intended to acquire an overview of how the process of policy implementation done recording service and civilian population, especially in the implementation of the e-KTP program in the Melawi regency. title of this essay is obtained based on the phenomenon that is happening on the implementation of e-KTP program that has not reached a predetermined target. In this study researchers used primarily to descriptive research using qualitative methods. subjects in this study is that the official government population and civil registration as the implementor and the people involved in the implementation of this policy of the e-ktp card. data collection techniques used were interview, observation and documentation. Conclusion of this research is the implementation of e-ktp card program has not been able to achieve the set targets due to several factors which is the bottleneck in the implementation of resource factors that include human resources and equipment resources. Keywords: Policy, Implementation, Program, E-KTP Card.